2013
DOI: 10.1111/jasp.12060
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and subordinate emotional labor: The moderating role of openness personality

Abstract: We investigated the differential relationships between abusive supervision and two emotional labor strategies used by subordinates (surface acting and deep acting). Furthermore, we examined whether subordinates' openness personality moderated the above relationships. Using the questionnaire survey method, we collected data from 210 employees in China. The results of hierarchical regression showed that abusive supervision related positively to surface acting (regulating facial expression) but negatively to deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 83 publications
2
47
0
6
Order By: Relevance
“…We also controlled for gender similarity because some evidence suggests that men are typically bullied by other men and often by supervisors while women may face victimization from both other women and men (Salin, 2003;Zapf, Escartin, Hoel, & Vartia, 2011;Cortina et al, 2002). Finally, we controlled for tenure under current supervisor and subordinate hierarchical level because previous studies found significant relationships between these demographics and individual perceptions of abusive supervision (Wu & Hu, 2013).…”
Section: Control Variablesmentioning
confidence: 99%
“…We also controlled for gender similarity because some evidence suggests that men are typically bullied by other men and often by supervisors while women may face victimization from both other women and men (Salin, 2003;Zapf, Escartin, Hoel, & Vartia, 2011;Cortina et al, 2002). Finally, we controlled for tenure under current supervisor and subordinate hierarchical level because previous studies found significant relationships between these demographics and individual perceptions of abusive supervision (Wu & Hu, 2013).…”
Section: Control Variablesmentioning
confidence: 99%
“…According to the theory of resource conservation, individuals with fewer resources are likely to not suffer more loss to enter the loss cycle. In the workplace, some researchers [24] found that abusive subordinates perceive the potential loss of resources associated with social support and cause emotional exhaustion. To Y. Pan prevent further loss of resources, they may choose to avoid feedback [25].…”
Section: Resource Levelmentioning
confidence: 99%
“…이러한 관점에서 조직지원인식 은 구성원에게 보답의 의무감을 가지게 하고, 결과적으로 조직에 대한 정서적 몰입이나 조 직의 목표달성을 위한 구성원의 노력이 동반 되며, 직무성과, 조직몰입과 같은 바람직한 반 응행동으로 나타날 수 있다 (Armeli, Eisenberger, Fasolo, & Lynch, 1998;Eisenberger et al, 1986;Rhoades & Eisenberger, 2002 (Halbesleben, 2006) 전자는 지원의 원천을 개인(대인관계)에게서 찾는 반 면(예: Cohen & Wills, 1985;Leavy, 1983), 후자 는 의인화한 조직으로부터의 재정적, 물리적, 사회․정서적 지원 등을 포함한다는 점에서 (Duke et al, 2009;Eisenberger et al, 1986;Halbesleben, 2006 (Jawahar et al, 2007;Stamper & Johlke, 2003 (Brotheridge & Lee, 2002;Kammeyer-Mueller et al, 2013), 경험한 정서와 표현한 정서의 차이로 인해 정서부조화를 경험하게 된다는 것을 의미한다 (Ashforth & Humphrey, 1993;Brotheridge & Grandey, 2002 (Mann, 1999;Rafaeli & Sutton, 1987), 그 결과 직무에 대한 효능감 감 소로 이어져 직무열의를 감소시킬 수 있다는 설명도 가능하다. 마지막으로 정서를 가장하 는 행위 자체는 직무에 대해 열의를 느끼고 있지 않는 상태로 보는 것이 적절할 수 있다 (Wu & Hu, 2013). 그러나 선행 연구에서 표면 행동과 직무열의 간 유의한 관계가 나타나지 않았기 때문에 (신강현 등, 2008; 박선애, 이재 창, 2014), 해석에 주의할 필요가 있다.…”
Section: 위와 같은unclassified
“…특히 이러한 개연성은 상사와 부하직원 간 관계에서 존재할 수 있다. 실제로 상사는 부 하직원의 연봉이나 승진에 영향을 미치는 사 회적 권력을 가지고 있기 때문에 (Tepper, 2000;Wu & Hu, 2013), 동료나 부하 보다 상사에 대 한 정서 표현이 상대적으로 어려울 수 있다. 또한 우리나라와 같은 집단주의 문화권에서 부하직원은 상사의 독단적인 리더십에 인내하 는 경향이 있는 것으로 볼 때 (Hui, Yee, & Eastman, 1995), 상사에게 자신의 감정을 관리 해야만 하는 상황에 직면할 가능성은 높다.…”
unclassified